2021
DOI: 10.1039/d0ew00911c
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate removal from reverse osmosis concentrate in pilot-scale open-water unit process wetlands

Abstract: Biological treatment of nitrate in reverse osmosis (RO) concentrate produced from municipal wastewater effluent is challenging, in part because of the low carbon-to-nitrogen ratio. Open-water unit process wetlands may provide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…The faster removal observed in 2019 was consistent with greater biomat activity in 2019 compared to 2018, which was supported by observations of greater biomat depth and nitrate removal capacity in 2019. 31 As predicted, removal rates declined during the cooler, winter months.…”
Section: Phototransformationmentioning
confidence: 55%
See 3 more Smart Citations
“…The faster removal observed in 2019 was consistent with greater biomat activity in 2019 compared to 2018, which was supported by observations of greater biomat depth and nitrate removal capacity in 2019. 31 As predicted, removal rates declined during the cooler, winter months.…”
Section: Phototransformationmentioning
confidence: 55%
“…31 Notably, although pH and dissolved oxygen profiles indicated strong photosynthetic activity within one month of startup, the biomat microbial community evolved throughout the first 18 months of operation and greater nitrate removal in the biomat was observed in summer 2019 compared to summer 2018. 31 Removal of atenolol and metoprolol was consistent with predictions from biotransformation models developed for open-water wetlands treating wastewater effluent (Figure 2). 29 During the summer 2018, calculated rate constants in the cell without ozone pre-treatment (Cell 1) averaged 0.50 d -1 and 0.48 d -1 for atenolol and metoprolol, respectively, which were similar to the predicted rate constants of 0.57 d -1 and 0.43 d -1 .…”
Section: Phototransformationmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, removing these P-containing organophosphonate compounds from ROC before its further treatment or discharge is imperative [26]. Scholes et al [27] revealed that open-water wetlands can remove nitrate from RO concentrate at the pilot scale and identified opportunities to enhance treatment efficiency with low-cost carbon amendments.…”
Section: Introductionmentioning
confidence: 99%